The Effect of Inflation, Exchange Rates, Interest Rates and Net Profits on Stock Prices in Food and Beverage Sub-Sector Companies on the IDX 2015-2019 - Afril Liantito Manurung; Melia Atania Ginting; Riris Yuli Mentari R.; Apriyanita Br Ginting; Wirda Lilia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the effect of inflation, exchange rates, interest rates and net income on stock prices in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange 2015-2019. The data used is sourced from annual report data on the Indonesia Stock Exchange through the websitewww.idx.co.id, and has been selected based on predetermined criteria. The population used in this study were all food and beverage sub-sector companies totaling 23 companies, using a purposive sample obtained as many as 40 samples. With this research, it is hoped that it can become a science to help further researchers and also students or the general public who need a source of information. From this study, it can be seen that inflation, exchange rates partially have no effect and have no significant effect on stock prices in the Food and Beverage Sub-Sector while Interest Rates and Net Profits partially have a significant effect on stock prices in the Food and Beverage Sub-sector. Drink. And all variables simultaneously affect the dependent variable. The choice of sector in this study is because Indonesia has now entered a more advanced era of globalization, of course there will be many foreign and local immigrants who will definitely need a variety of basic needs, so that many businesses or companies are built on that basis, which makes us intend to research it.